Kontribusi Komite Madrasah Dalam Peningkatan Mutu Sarana Dan Prasarana di Madrasah Aliyah Madani Alauddin - St. Ibrah Mustafa Kamal; St. Syamsudduha; Annisa Trifirjayani (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2022)
This study discusses the contribution of the Madrasah committee in improving the quality of facilities and infrastructure at Madrasah Aliyah Madani Alauddin. By describing: An overview of improving the quality of facilities and infrastructure in Madrasah Aliyah Madani Alauddin; The form of the Madrasah committee's contribution in improving the quality of facilities and infrastructure at Madrasah Aliyah Madani Alauddin; Supporting and inhibiting factors of the Madrasah committee in the provision of facilities and infrastructure at Madrasah Aliyah Madani Alauddin. This research is a type of explanatory research using research data collection methods, namely interviews, observation, and documentation. The results of this study indicate that improving the quality of facilities and infrastructure at Madrasah Aliyah Madani Alauddin is evidenced in terms of adding tools in the classroom. In addition, Madrasahs have made use of the land they own. The contribution of the Madrasah committee in improving Madrasah Aliyah Madani Alauddin is carried out by providing committees as: Advisory Agency, Supporting Agency, Controlling agency, Mediator agency. The research implication is that madrasas can increase cooperation to increase the management potential of Madrasah infrastructure, further improve the understanding of all parents/guardians of students in providing support to the committee